Effect of PMM Utilization, Academic Supervision, and Job Satisfaction on Teacher Performance in Biduk-Biduk State Elementary Schools - Nurdiansari, Nurdiansari; Nurlaili, Nurlaili; Haeruddin, Haeruddin (UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Improving the quality of education in coastal regions, such as the Biduk-Biduk Sub-district of Berau Regency, presents multifaceted challenges, particularly in enhancing teacher performance. This study was driven by preliminary indications of limited use of the Platform Merdeka Mengajar (PMM), insufficient academic supervision, and low levels of teacher job satisfaction. Employing a quantitative research design with a survey method, the study targeted 133 public elementary school teachers, from which 101 respondents were selected through proportional random sampling. Data analysis using multiple linear regression revealed that the utilization of PMM, academic supervision, and job satisfaction each had a significant positive impact on teacher performance. These findings underscore the strategic importance of integrating digital learning platforms, strengthening academic supervisory mechanisms, and fostering a supportive work environment to enhance teacher effectiveness. The study provides valuable insights for policymakers and education stakeholders aiming to improve educational quality in underdeveloped and geographically challenged coastal areas.